2023
DOI: 10.1002/bit.28487
|View full text |Cite
|
Sign up to set email alerts
|

The synergetic effect from the combination of different adsorption resins in batch and semi‐continuous cultivations of S. Cerevisiae cell factories to produce acetylated Taxanes precursors of the anticancer drug Taxol

Abstract: In situ product recovery is an efficient way to intensify bioprocesses as it can perform adsorption of the desired natural products in the cultivation. However, it is common to use only one adsorbent (liquid or solid) to perform the product recovery. For this study, the use of an in situ product recovery method with three combined commercial resins (HP‐20, XAD7HP, and HP‐2MG) with different chemical properties was performed. A new yeast strain of Saccharomyces cerevisiae was engineered using CRISPR Cas9 (strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…While in our previous work (Santoyo-Garcia et al 2023 ) we reported the effectiveness of the combination of resins HP-20, XAD7HP and HP-2MG in recovering taxanes from yeast cell factories, it is important to mention that our findings have not been directly applied to plant VSCs cells. The physical–chemical differences of these macro-porous commercial resins can be found in Santoyo-Garcia et al ( 2023 ). In addition, the main physical–chemical properties are described in Table 1 .…”
Section: Introductionmentioning
confidence: 79%
See 4 more Smart Citations
“…While in our previous work (Santoyo-Garcia et al 2023 ) we reported the effectiveness of the combination of resins HP-20, XAD7HP and HP-2MG in recovering taxanes from yeast cell factories, it is important to mention that our findings have not been directly applied to plant VSCs cells. The physical–chemical differences of these macro-porous commercial resins can be found in Santoyo-Garcia et al ( 2023 ). In addition, the main physical–chemical properties are described in Table 1 .…”
Section: Introductionmentioning
confidence: 79%
“…Next, we determined the impact of combinations of these resins on in situ cultivation of VSCs at different resin concentrations and configurations to test the impact on both cell growth and taxane production, as the combination of these three resins has shown favourable results for purification of taxanes from recombinant yeast expressing some of the known paclitaxel pathway enzymes (Santoyo-Garcia et al 2023 ). Treatments consisting of three combinations of resins were employed (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations